2022
DOI: 10.3390/ijerph19116858
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Cross-Cultural Adaptation, and Validation of the Malay Version of the Protection Motivation Theory Scale Questionnaire for Pap Smear Screening

Abstract: Pap smear screening can detect cervical cancer early, but is underutilized. Motivational factors play a role in ensuring that women undergo Pap smear screening. This study was conducted to validate the adapted instrument, which was based on the protection motivation theory (PMT), into the Malay language to evaluate the motivational factors for Pap smear screening among women. The original 26-item PMT scale was developed based on seven constructs of the PMT framework. The adaptation involved translation by bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Good constructs achieve when factor loading >0.40. Before CFA was conducted, Keyser-Meyer-Olkin (KMO) and Bartlett's test were conducted to measure sampling adequacy [ 16 ]. The KMO value was divided into several ranges: KMO ≥ 0.6 means low adequacy, KMO ≥ 0.7 means moderate adequacy, KMO ≥ 0.8 means high adequacy, and KMO ≥ 0.9 means very high [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good constructs achieve when factor loading >0.40. Before CFA was conducted, Keyser-Meyer-Olkin (KMO) and Bartlett's test were conducted to measure sampling adequacy [ 16 ]. The KMO value was divided into several ranges: KMO ≥ 0.6 means low adequacy, KMO ≥ 0.7 means moderate adequacy, KMO ≥ 0.8 means high adequacy, and KMO ≥ 0.9 means very high [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire is valid if Pearson’s correlation shows p <0.05 and has good construct validity (CFA >0.4) [ 15 , 16 ]. It was said to be reliable if Cronbach’s Alpha had a value of >0.70 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…When faced with a threat such as CC, a person will first appraise it based on how likely it can affect them (perceived vulnerability), how bad it is (perceived severity), and its potential consequences (fear appraisal). Subsequently, the person decides how the threat (CC) can be reduced by determining how likely they could perform the required behavior, i.e., CC screening (self-efficacy), evaluate the potential cost (response cost), and the resources in performing such behavior (response efficacy) ( Li et al, 2020 , Romli et al, 2022 , Hassani et al, 2014 ). Intervention studies that focused on motivations used these seven PMT constructs as important elements and reported that the effects were evident ( Malmir et al, 2018 , Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%